2012
DOI: 10.1016/j.foodres.2012.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive peptides in water-soluble extracts of ovine cheeses from Southern Brazil and Uruguay

Abstract: Water soluble extracts (WSE) of ewe's cheeses produced in Uruguay and Brazil were evaluated for their biological activities. Feta-type, Roquefort-type and Pecorino-type cheeses from Brazil, Pecorino Sardotype and Cerrillano cheese samples from Uruguay, were analyzed. Antioxidant properties were evaluated using distinct methods. Scavenging of the cation radical of 2,2′-azino-bis-(3-ethylbenzothiazoline)-6-sulfonic acid (ABTS) ranged from 32 to 45% for Feta-type cheeses to 87% for Roquefort-type cheese. A simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 38 publications
8
57
0
6
Order By: Relevance
“…9 of the detected peptides manifested a strong antioxidant activity, and were a product of β-CN proteolysis, more precisely they originated from the fragment f207-221 (QEPV-LGPVRGPFPIL). Meira et al (2012) discussed the antioxidant activity of water-soluble extracts from three Brazilian cheeses (Feta-type, Roqueforttype and Pecorino-type cheese) and two Uruguayan cheeses (Pecorino Sardo-type and Cerrilano-type) and showed that type of cheese substantially determined the content and antioxidant activity of water-soluble extracts. Accordingly, the Roqueforttype cheese had the highest content and the highest antioxidant capacity.…”
Section: Antioxidant Peptides Of White Cheese In Brinementioning
confidence: 99%
“…9 of the detected peptides manifested a strong antioxidant activity, and were a product of β-CN proteolysis, more precisely they originated from the fragment f207-221 (QEPV-LGPVRGPFPIL). Meira et al (2012) discussed the antioxidant activity of water-soluble extracts from three Brazilian cheeses (Feta-type, Roqueforttype and Pecorino-type cheese) and two Uruguayan cheeses (Pecorino Sardo-type and Cerrilano-type) and showed that type of cheese substantially determined the content and antioxidant activity of water-soluble extracts. Accordingly, the Roqueforttype cheese had the highest content and the highest antioxidant capacity.…”
Section: Antioxidant Peptides Of White Cheese In Brinementioning
confidence: 99%
“…Results revealed that bioactive peptides behave differently towards different radicals depending on their medium of solubility. ABTS radical being water soluble in nature is reduced easily by the peptides which are able to donate hydrogen but to become a stable diamagnetic molecule, DPPH accepts hydrogen in oil medium (Phanturat, Benjakul, Visessanguan, & Roytrakul, 2010) thus not targeted by bioactive peptides soluble in aqueous medium (Meira et al, 2012). ABTS radical scavenging ability increased significantly (P 0.05) whereas no significant (P 0.05) change was observed in DPPH radical scavenging activity which was due to the reason already discussed above.…”
Section: Antioxidant Assaysmentioning
confidence: 79%
“…Pritchard et al (2010) identified antimicrobial activities against Escherichia coli ATCC 8739 and Bacillus cereus ATCC 11778 in WSEs isolated from Australian Cheddar cheese. Meira et al (2012) examined no antimicrobial effect in WSEs obtained from ripened sheep cheeses. Rizzello et al (2005) determined no antimicrobial activity in WSEs isolated from Fossa cheese produced with sheep milk as well.…”
Section: Resultsmentioning
confidence: 99%
“…Chromatogram results are given from the 0th, 60th, and 120th days from bottom to top. cow and goat milk Tulum cheeses were higher than Roquefort, Cerrillano, and Pecorine-type cheeses produced using sheep milk (Meira et al, 2012). Goat milk Tulum cheese had significantly higher chelating activity than cow milk Tulum cheese (P < 0.01).…”
Section: Chromatographic Profiles Of Tulum Cheese Peptides By Rp-hplcmentioning
confidence: 85%